2015
DOI: 10.1088/0264-9381/32/11/115012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the LIGO detectors during their sixth science run

Abstract: In 2009-2010, the Laser Interferometer Gravitational-wave Observatory (LIGO) operated together with international partners Virgo and GEO600 as a network to search for gravitational waves of astrophysical origin. The sensitivity of these detectors was limited by a combination of noise sources inherent to the instrumental design and its environment, often localized in time or frequency, that couple into the gravitational-wave readout. Here we review the performance of the LIGO instruments during this epoch, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
498
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,172 publications
(513 citation statements)
references
References 51 publications
2
498
1
Order By: Relevance
“…We direct the reader to Kalmus [176], in which it is shown that phase uncertainties contribute negligibly to the total systematic error, and thus we only consider amplitude uncertainties in this study. The target design amplitude uncertainties in the frequency range 40-2048 Hz for Advanced LIGO and Advanced Virgo are 5% at 2σ confidence [177]. As such, the upper limits for h 50% rss and d 50% obtained from a search for GWs from CCSNe in the Advanced detector era will have intrinsic ∼5% uncertainties.…”
Section: E Systematical Uncertaintiesmentioning
confidence: 95%
See 1 more Smart Citation
“…We direct the reader to Kalmus [176], in which it is shown that phase uncertainties contribute negligibly to the total systematic error, and thus we only consider amplitude uncertainties in this study. The target design amplitude uncertainties in the frequency range 40-2048 Hz for Advanced LIGO and Advanced Virgo are 5% at 2σ confidence [177]. As such, the upper limits for h 50% rss and d 50% obtained from a search for GWs from CCSNe in the Advanced detector era will have intrinsic ∼5% uncertainties.…”
Section: E Systematical Uncertaintiesmentioning
confidence: 95%
“…Noise in interferometers arises from a combination of instrumental, environmental, and anthropomorphic noise sources that are extremely difficult to characterize precisely [50,[99][100][101]. Instrumental "glitches" can lead to large excursions over the time-averaged noise and may mimic the expected time-frequency content of an astrophysical signal [50,102].…”
Section: B the Duty Cycle Of The Detectors Is Not 100%mentioning
confidence: 99%
“…A classic discussion of the noise sources for such an interferometer is given by Weiss [25]; remarkably, even his estimates for the magnitudes of the noise sources hold up well today (see [26] for a recent characterization of the detectors). In the LIGO detectors, as well as in GEO600, Virgo (currently being upgraded), KAGRA (currently being constructed), and the planned LIGO-India detector (see [27] for a recent discussion of the status of several of these detectors; note that final approval for LIGO-India was given just a week after the announcement of the GW150914 event), the instrument is L-shaped, with equal arm lengths that range from 600 meters (GEO600) to 4 km (LIGO and LIGO-India).…”
Section: Gravitational-wave Detectorsmentioning
confidence: 99%
“…[5], while still assuming ideal conditions on the data, a framework to distribute the total available computing cost between different possible targets based on astrophysical priors has been developed. However under realistic conditions the available data, as collected for example from the Laser Interferometer Gravitational-Wave Observatory (LIGO) [6,7], can be fragmented, e.g., due to down-time of the detectors, and there might be variations in the noise floor. The fragmentation of the data can significantly affect the computing cost function and thus the optimal search parameters.…”
Section: Introductionmentioning
confidence: 99%